Robust arterial spin labeling MRI measurement of pharmacologically induced perfusion change in rat kidneys. (6th June 2021) - Zhao, Fuqiang; Zhou, Xiaoyan; Messina, Eric; Hu, Lufei; Holahan, Marie A.; Swaminath, Gayathri; Hines, Catherine D. G.
Abstract : Kidney diseases such as acute kidney injury, diabetic nephropathy and chronic kidney disease (CKD) are related to dysfunctions of the microvasculature in the kidney causing a decrease in renal blood perfusion (RBP). Pharmacological intervention to improve the function of the microvasculature is a viable strategy for the potential treatment of these diseases. The measurement of RBP is a reliable biomarker to evaluate the efficacy of pharmacological agents' actions on the microvasculature, and measurement of RBP responses to different pharmacological agents can also help elucidate the mechanism of hemodynamic regulation in the kidney. Magnetic resonance imaging (MRI) with flow‐sensitive alternating inversion recovery (FAIR) arterial spin labeling (ASL) has been used to measure RBP in humans and animals. However, artifacts caused by respiratory and peristaltic motions limit the potential of FAIR ASL in drug discovery and kidney research. In this study, the combined anesthesia protocol of inactin with a low dose of isoflurane was used to fully suppress peristalsis in rats, which were ventilated with an MRI‐synchronized ventilator. FAIR ASL data were acquired in eight axial slices using a single‐shot, gradient‐echo, echo‐planar imaging (EPI) sequence. The artifacts in the FAIR ASL RBP measurement due to respiratory and peristaltic motions were substantially eliminated. The RBP responses to fenoldopam and L‐NAME were measured, and the increase and decrease in RBP caused by fenoldopam and L‐NAME, respectively, were robustly observed. To further validate FAIR ASL, the renal blood flow (RBF) responses to the same agents were measured by an invasive perivascular flow probe method. The pharmacological agent‐induced responses in RBP and RBF are similar. This indicates that FAIR ASL has the sensitivity to measure pharmacologically induced changes in RBP. FAIR ASL with multislice EPI can be a valuable tool for supporting drug discovery, and for elucidating the mechanism of hemodynamic regulation in kidneys. Abstract : FAIR ASL measurement of renal blood perfusion (RBP). Control (nsIR) images (top row) and labeled (ssIR) images (middle row) from four axial slices were acquired by ventilation‐synchronized single‐shot EPI. Sharp edges between the kidney and surrounding tissues are observed due to the fast imaging EPI sequence. Corresponding RBP‐weighted images were calculated by subtracting the labeled/control images. The high signal intensity in the kidney cortex reveals high blood perfusions to the cortex.